Трое на четырех колесах: [сборник : перевод с английского] - Джером Клапка Джером (Мировая классика, 2007)
Экземпляры: СФ-8 (20110920) / Инвентарный номер: 35537z8 / Цена: 102.41 / Сис.шифр: 84(4Вел) / Авт.знак: Д 40 / ГРНТИ: 17.82.82 / ББК: 84(4Вел)